Ramsar wetlands in Nepal: Status, uses, challenges, and conservation strategies – a review - Timalsina, Rojesh; Maharjan, Shreejala; Kandel, Shusila; Awasthi, Mahesh Prasad; Bishwakarma, Kiran; Dhami, Urmila; Thapa, Lal Bahadur; Singh, Virendra Bahadur; Pant, Ramesh Raj (Nepalese Journal of Zoology, 2025)
The wetlands of Nepal extend from the lowlands of Tarai to the high Himalayas, supporting biodiversity and livelihoods by providing valuable goods and services. This research is based on the published literature at both national and international levels, discussing the geographical distribution, status, major benefits, threats and management strategies for the wetlands of Nepal. Nepal hosts only two categories of wetlands, as a Ramsar Site i.e., natural freshwater and manmade wetlands. Ramsar sites of Nepal comprises of ten wetlands i.e., nine natural freshwater and one manmade. Total estimated area of the wetlands is about 8192.77 km2, while Ramsar sites cover a surface area of 605.61 km2. Despite their ecological significance, these wetlands are facing immense pressure from factors like global climate change, population growth, haphazard development, urbanization, land use changes and the shrinkage of watershed areas. Although various policies and the presence of a legal framework, there is no effective institution for the management of wetlands in Nepal. To ensure sustainable management of the wetlands, it is imperative to establish a dedicated and effective institution at federal, provincial and local levels, enhance coordination among the stakeholders and implement comprehensive conservation strategies.